The Power of the Agile Business Analyst, 2nd Edition - 30 Surprising Ways A Business Analyst Can Add Value To Your Agile Development Team (Audio Book) - Cooke, Jamie (IT Governance Publishing, 2018)
Drawing on her extensive experience, Jamie proposes a new role for Agile projects: The Agile business analyst. She details 30 achievable ways that such a role will increase relevance, quality and overall business value, and provide business users with crucial support.